Impact of ethanol blending policies on U.S. gasoline prices - Janda, Karel,Letovska, Vendula,Sila, Jan,Zilberman, David (Institute of Economic Studies, Faculty of Social Sciences, Charles University in Prague, 2024)
This paper investigates the impact of ethanol blending mandates on retail fuel prices in the United States. It uses the modifications of three microeconomics models - partial equilibrium theoretical model by de Gorter and Just, partial equilibrium simulation model of Drabik et al. and Wu and Langpap general equilibrium model - on historical data from 2009 to 2022 and predictive data from 2023 to 2030, sourced from the U.S. Energy Information Administration (EIA) and the United States Department of Agriculture (USDA), to simulate scenarios involving various ethanol blend rates. The findings reject the hypothesis that increasing ethanol blend rates always lead to higher fuel prices.
10419/303258
Keywords: Graue Literatur; biofuels; ethanol; fuel prices; renewable fuel standard